THE EFFECT OF FINANCIAL LITERACY AND DEMOGRAPHICS ON THE SAVING BEHAVIOR OF THE MILLENNIAL GENERATION - Stephanie Lie; Dewi Astuti; Mariana Ing Malelak (Finance and Investment Program, School of Business and Management - Petra Christian University, 2022)
This study aims to determine the influence of financial literacy and demographics on the saving behavior of the millennial generation in Kupang City. This research was conducted by distributing online questionnaires and face-to-face to the millennial generation in Kupang City. In this study, as many as 100 respondents were used. The researcher used dummy variable regression. The results of the analysis show that financial literacy, dummy income 2 and 3, education level, age, and gender do not have a significant effect on the saving behavior of the millennial generation in Kupang City. Dummy income 1 has a significant effect on the saving behavior of the millennial generation in Kupang City.